1999
DOI: 10.1007/s101470050024
|View full text |Cite
|
Sign up to set email alerts
|

Primary chemotherapy in strongly suspected yolk sac tumor of the ovary

Abstract: We report a case of a right ovarian tumor measuring 10.8 ϫ 10 ϫ 8.5 cm (diagnosed as a yolk sac tumor) in a 31-year-old nulligravid woman with serum α-fetoprotein (AFP) level of 25 000 ng/ml and pleural effusion. Seven courses of primary chemotherapy (PVB; cisplatin, vinblastine, bleomycin) were given from May 16 to November 11, 1994. No surgical procedures were conducted. After the second course of PVB, the pleural effusion resolved; after the third course, the tumor disappeared, and after the fourth course, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The study selection was performed as shown in Figure 1 . A total of 141 articles were screened, and 15 studies, comprising 142 women with MOGCT treated with NACT versus 387 women with MOGCT treated without NACT, met the inclusion criteria for the present systematic review [ 5 , 6 , 7 , 9 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. After the identification of eligible studies, we checked the reference lists of all eligible studies and confirmed that potential citations/studies were not missed during the literature screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection was performed as shown in Figure 1 . A total of 141 articles were screened, and 15 studies, comprising 142 women with MOGCT treated with NACT versus 387 women with MOGCT treated without NACT, met the inclusion criteria for the present systematic review [ 5 , 6 , 7 , 9 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. After the identification of eligible studies, we checked the reference lists of all eligible studies and confirmed that potential citations/studies were not missed during the literature screening.…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies ( n = 15) were retrospective in nature and were published between 1999 and 2023. Of these 15 studies, 10 were original articles [ 9 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 ] and five were case reports [ 5 , 6 , 7 , 35 , 38 ]. Approximately half of the studies ( n = 8) were conducted in India [ 6 , 28 , 30 , 31 , 32 , 34 , 35 , 36 ], followed by China ( n = 2) [ 9 , 33 ] and others ( n = 1: England, France, Spain, Thailand, and Japan) [ 5 , 7 , 29 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation